Molecular investigations of Hepatozoon species in dogs and developmental stages of Rhipicephalus sanguineus - Aktas, Munir; Ozubek, Sezayi; Ipek, Duygu Neval Sayin (Springer, 2013)
The occurrence and distribution of Hepatozoon species in stray dogs, and the developmental stages of Rhipicephalus sanguineus detached from the same dogs in DiyarbakA +/- r Province, Turkey is reported. A total of 328 ticks, including 133 adults (55 males and 75 females consist of 63 partially engorged and 15 fully engorged) and 195 nymphs (91 partially engorged and 104 fully engorged) were detached from the dogs. Fully engorged nymphs and females were incubated at 27 A degrees C and relative humidity of 85 % to molt to adult stage and recover eggs. The ticks were pooled according to sex and developmental stage. No Hepatozoon gamonts were found, whereas, by PCR, 15.87 % (10/63) of the dogs were infected with Hepatozoon canis. Of the 68 tick pools tested, 14 (20.58 %) pools were infected with Hepatozoon spp., an overall maximum likelihood estimation of prevalence of 4.9 % (95 % confidence intervals (CI) = 2.85-7.93 %) per 100 ticks. Maximum likelihood estimation of the infection rate varied by tick sex and developmental categories, ranging from 1.75 % (95 % CI = 0.11-8.11 %) in fed males to 6.81 % (95 % CI = 2.07-17.46 %) in unfed females. One amplicon from a fed adult female was 99 % identical to the sequence for Hepatozoon felis. The remaining sequences isolated from both dogs and ticks shared 99-100 % similarity with the corresponding H. canis isolates. This is the first detection of H. canis and H. felis in the tick R. sanguineus in Turkey.
Keywords: Canis Infection; Borne Infections; Cats; Apicomplexa; Tick; Adeleorina